Pengembangan Media Pembelajaran Peralatan Multimedia berbasis Augmented Reality dengan Outfit Marker di SMK Hayam Wuruk Mojokerto - Mei Mukti Wardana; Tri Afirianto; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
There are limitations in accessing multimedia equipment props due to the pandemic conditions imposed by distance or online learning at SMK Hayam Wuruk Mojokerto. Not all students have teaching aids to be used as learning media. Therefore, an augmented reality-based Android application was created to provide a real picture of the props. This study uses the waterfall model and unified modeling language (UML) when designing an Android application. The development was carried out using Unity and Vuforia to produce an augmented reality based learning media. Android application testing is carried out to determine whether the application will have minimal errors or is feasible to use by using two techniques, namely black box testing and usability testing. Validation of media application is carried out by media expert, teacher and students using usability testing and a Likert scale of 1-5 through a questionnaire. Usability testing that has been tested by media experts, teachers and students shows that this application has "Good" criteria to be used as additional learning media. From the test results, it can be concluded that the augmented reality Based Learning Media Development of Multimedia Equipment with Outfit Marker can be said to be suitable for use as learning media.